Using Metabolomics to Assist Plant Breeding - Alseekh, Saleh; Fernie, Alisdair R (Methods in molecular biology (Clifton, N.J.), 2021)
Recent methodological advances in both gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS) have provided a deep understanding of metabolic regulation occurring in plant cells. The application of these techniques to agricultural systems is, however, subject to more complex interactions. Here we summarize a step-by-step modern metabolomics methodology that generates metabolome data toward the implementation of metabolomics in crop breeding. We describe a metabolic workflow, and provide guidelines for handling large sample numbers for the specific purpose of metabolic quantitative trait loci approaches.